2023
DOI: 10.21833/ijaas.2023.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of entrepreneurial competencies using Scopus data and VOSviewer

Abstract: The positive impact of entrepreneurial competencies has sparked the attention of researchers from various industries and disciplines. Since academic scholars are becoming more interested in the practice of entrepreneurial competencies, thus it is required to gain a better grasp of the themes of interest and to expand collaboration networks in order to advance research toward interdisciplinary approaches. Therefore, an analysis using the bibliometric technique was conducted to find major trends and themes by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…In line with previous research (Lackéus and Sävetun 2019;Luis-Rico et al 2020;Manickam and Abd Rozan 2023;Schelfhout et al 2016;Susantiningrum et al 2023), the results obtained suggest that entrepreneurship education has a positive effect on participants in such education programmes. Specifically, the data on the first hypothesis (the formation of entrepreneurial attitudes will significantly increase the entrepreneurial potential of the participating students) revealed that, after implementing the programme, the scores for the experimental group had increased, and were significantly higher than those of the control group, for the five attitudes studied.…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous research (Lackéus and Sävetun 2019;Luis-Rico et al 2020;Manickam and Abd Rozan 2023;Schelfhout et al 2016;Susantiningrum et al 2023), the results obtained suggest that entrepreneurship education has a positive effect on participants in such education programmes. Specifically, the data on the first hypothesis (the formation of entrepreneurial attitudes will significantly increase the entrepreneurial potential of the participating students) revealed that, after implementing the programme, the scores for the experimental group had increased, and were significantly higher than those of the control group, for the five attitudes studied.…”
Section: Discussionsupporting
confidence: 91%